Is Clinical Evaluation Sufficient for Decision Making in Patients With Penetrating Abdominal Trauma? - Ahmad Izadpanah (Shiraz University of Medical Sciences, 2015)
Background Functional gastrointestinal (GI) disorders are very common and many patients with such disorders are not satisfied with treatment outcomes. Psychological aspects of functional disorders need special attention that may play an important role in patient management. Objectives In this study, psychology evaluation was performed for a population of patients with functional bowel disorders. Patients and Methods One hundred patients with functional bowel disorders including 50 patients with irritable bowel syndrome (IBS) referred to GI clinics were candidates for psychiatry evaluation; of those 60 patients completed the study. Psychiatric disorders were diagnosed using a structured clinical interview based on diagnostic and statistical manual of mental disorders IV (DSM IV). Results Of 60 patients with functional bowel disorders (including 39 IBS), 51 (85%) were diagnosed with at least one psychiatry disorder. The most common disorders were dysthymia (25%) and obsessive-compulsive disorder (20%). There was no significant difference between IBS patients and other functional bowel disorders regarding the prevalence of psychiatric disorders. Conclusions Psychiatric disorders are very prevalent among patients with functional bowel disorders. Prompt diagnosis and appropriate management of associated psychiatric disorders along with GI targeted treatments may lead to a better outcome in these patients.